Pengaruh Kesehatan Kerja dan SOP Produksi ISO 9001 terhadap Kualitas Kerja Karyawan (Studi Kasus pada Perusahaan Karet) - Ardianto, Marcelinus Bily; Astono, Anjar Dwi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
This study aims to determine the effect of occupational health and ISO 9001 production SOP on the quality of work of employees in a rubber company. This study uses a quantitative approach. This research was condcted with the unit analysis of Rubber Companies, with a population of 41 people. The sampling method used is Non-Probability sampling, with a saturated sample type, sampling with a total of 41 respondents, with a questionnaire data collection technique. Data processing method using multiple linear regression analysis. The results of this study concluded that there is a significant effect of occupational health on employee work quality, there is a significant effect of ISO 9001 production SOP on employee work quality, and there is a significant simultaneous influence between occupational health variables and ISO 9001 production SOP on employee work quality.